2015
DOI: 10.1089/jpm.2014.0265
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Case Finding To Improve Concurrently Curative and Palliative Care in Patients with End-Stage Liver Disease

Abstract: Background: Palliative care and preparation for liver transplantation are often perceived as conflicting for patients with end-stage liver disease (ESLD). We sought to improve both simultaneously through a case finding and care coordination quality improvement intervention. Methods: We identified patients with cirrhosis using validated ICD-9 codes and screened them for ESLD by assessing medical records at a VA hospital for either a model for end-stage liver disease (MELD) ‡ 14 or a diagnosis of hepatocellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…A few small studies have explored methods for integrating palliative care earlier in the care of patients with end-stage liver disease 29-31 ; however, guidelines regarding when to consider palliative care are needed. Our finding that transplantation listing or receipt is associated with lower odds of receiving inpatient palliative care mirrors findings from a previous study demonstrating an association between liver transplantation status and poorer end-of-life care quality 32 .…”
Section: Discussionmentioning
confidence: 99%
“…A few small studies have explored methods for integrating palliative care earlier in the care of patients with end-stage liver disease 29-31 ; however, guidelines regarding when to consider palliative care are needed. Our finding that transplantation listing or receipt is associated with lower odds of receiving inpatient palliative care mirrors findings from a previous study demonstrating an association between liver transplantation status and poorer end-of-life care quality 32 .…”
Section: Discussionmentioning
confidence: 99%
“…While concurrent palliative and hepatology care for patients on the waiting list has been described as feasible and effective, palliative care consults are rare even for patients denied transplant listing . Another strategy that has proven effective in the pre‐transplant setting is care coordination, which significantly increased transplant candidacy in one center (78% vs 31%) . Given the significant overlap between the experience of pain and psychiatric symptoms in the setting of cirrhosis, optimizing psychiatric management is certainly an important component of pain control.…”
Section: Discussionmentioning
confidence: 99%
“…A quality improvement study in a Veterans Affairs setting, designed to proactively identify patients with a Model for ESLD (MELD) score ≥ 14 and/or hepatocellular carcinoma (HCC); patients were referred for a PC consultation through a care coordinator. ( 43 ) The results showed that PC consultations improved the likelihood of being considered for LT and the likelihood of completing the transplantation evaluations. Telehealth could potentially be used to integrate PC within LT care, as has shown to work within liver practices.…”
Section: Structures and Processes Required For Integrating Nonhospicementioning
confidence: 96%